2021
DOI: 10.1093/ehjcr/ytab054
|View full text |Cite
|
Sign up to set email alerts
|

Sudden cardiac death risk in contact sports increased by myocarditis: a case series

Abstract: Background Myocarditis is a known cause of sudden cardiac death of the athlete. The impact of direct chest trauma in at-risk sports or activities in patients with a history of myocarditis has never been demonstrated or studied. We report herein two cases of life-threatening ventricular arrhythmia secondary to non-penetrating blunt chest trauma while playing contact sports. Case summary The first patient, a 26-year-old man des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Several quotes support the idea that both spike protein and mRNA are released within exosomes from vaccine-transfected cells, and that recipient cells can take up the mRNA and synthesize spike protein from it ( Trougakos et al, 2022 ; Maugeri et al, 2019 ; Mishra and Banerjea, 2021 ; Bansal et al, 2021 ; Qin and Dallas, 2019 ). We also provide several references, many of which were published after our paper was published, supporting both myocarditis and pericarditis risk increase in association with the vaccines ( Oster et al, 2022 ; Mörz, 2022 ; Mansanguan et al, 2022 ; Massoullié et al, 2021 ), as well as a lack of association of myocarditis with COVID-19 disease ( Sechi et al, 2021 ; Tuvali et al, 2022 ). Moreover, patients with solid tumors regularly develop autoantibodies post vaccination, including anti-cardiac atrial myosin heavy chain 6 (MHC-α), a clear immune-related adverse event associated with myocarditis.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Several quotes support the idea that both spike protein and mRNA are released within exosomes from vaccine-transfected cells, and that recipient cells can take up the mRNA and synthesize spike protein from it ( Trougakos et al, 2022 ; Maugeri et al, 2019 ; Mishra and Banerjea, 2021 ; Bansal et al, 2021 ; Qin and Dallas, 2019 ). We also provide several references, many of which were published after our paper was published, supporting both myocarditis and pericarditis risk increase in association with the vaccines ( Oster et al, 2022 ; Mörz, 2022 ; Mansanguan et al, 2022 ; Massoullié et al, 2021 ), as well as a lack of association of myocarditis with COVID-19 disease ( Sechi et al, 2021 ; Tuvali et al, 2022 ). Moreover, patients with solid tumors regularly develop autoantibodies post vaccination, including anti-cardiac atrial myosin heavy chain 6 (MHC-α), a clear immune-related adverse event associated with myocarditis.…”
mentioning
confidence: 61%
“… mRNA Vaccines, COVID-19 and Myocarditis ME Oster et al, 2022 "Based on passive surveillance reporting in the US, the risk of myocarditis after receiving mRNA-based COVID-19 vaccines was increased across multiple age and sex strata and was highest after the second vaccination dose in adolescent males and young men." S Mansanguan et al, 2022 “Cardiovascular manifestations were found in 29.24% of patients, ranging from tachycardia or palpitation to myopericarditis.” M Mörz, 2022 “Surprisingly, only spike protein but no nucleocapsid protein could be detected within the foci of inflammation in both the brain and the heart” “Since the nucleocapsid protein of SARS-CoV-2 was consistently absent, it must be assumed that the presence of spike protein in affected tissues was not due to an infection with SARS-CoV-2 but rather to the transfection of the tissues by the gene-based COVID-19-vaccines.” G Massoullié et al, 2021 "Myocarditis may increase the risk of life-threatening ventricular arrhythmias caused by blunt impact to the chest, particularly in contact sports. Screening and prevention measures should be considered to reduce this risk."…”
mentioning
confidence: 99%
“…However, it is accepted that a non-negligible percentage of sudden deaths occur due to myocarditis. Myocarditis is a major cause of sudden death among young people with an incidence that is twice as high in males than in females and is even more prevalent among athletes [21][22][23].…”
Section: Correlation Between Myocarditis and Sudden Deathmentioning
confidence: 99%
“…Autopsies have demonstrated that catecholamines triggered myocarditis following COVID-19 mRNA vaccination. The bridge connecting myocarditis and sudden death is found in the chronic hyperadrenergic state, a plausible and demonstrated cause [21][22][23]. Excessive long-term adrenaline and noradrenaline release, particularly at rest, is an independent predictor of sudden death [34,35].…”
Section: The Bridge Between Myocarditis and Sudden Death After Covid-...mentioning
confidence: 99%
“…The resting ECG test, which records the ECG signal of participants in rest, is typically taken as part of the routine checkups for people in clinic applications (10)(11). However, some heart abnormalities can be seen only during exercise (12), such as the common unexplained chest pain. The exercise ECG (eECG), which records the electrical signal of patients in exercise, is a widely used diagnostic procedure in the evaluation of both normal participants and cardiologic patients with coronary heart disease (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%